The conservation of the fish and other aquatic fauna of the North selangor peat swamp forest and adjacent areas (Asian Wetland Bureau, 1992)
This represents the largest single collection of blackwater species and new records. 101 species of fish were obtained, about 40% of the known fish fauna of Peninsular Malaysia,...